Appreciating Amartya Sen’s Thought for Religious Freedom in Indonesia - Muhammad, Iqtamar; Alfian, Andi (Prodi Sosiologi Agama, 2024)
The right to freedom of religion for everyone is regulated in the Constitution of the Unitary State of the Republic of Indonesia (NKRI). This right should be possessed and practiced properly for a better life of the nation and state. This research aims to appropriate Amartya Sen's thoughts for the practice of religious freedom in Indonesia. By tracing Amartya Sen's thoughts on freedom, this article seeks to ask questions such as how the pattern of religious freedom for citizens in Indonesia, which is pluralistic, and how the limits of religious freedom should be applied. This research uses two methods of data collection. First, the literature review method to trace the thoughts of Amartya Sen. Second, the netnography method to obtain data related to the practice of religious freedom in Indonesia. The data found were then analyzed using deductive-inductive content analysis techniques. After that, this research then appropriates Amartya Sen's thoughts for religious freedom in the Indonesian context. This research finds that religious freedom is the right of every citizen and the state should protect and guarantee these rights with the right mechanism.